Central nervous system involvement in mantle cell lymphoma: clinical features, prognostic factors and outcomes from the European Mantle Cell Lymphoma Network - Cheah CY; George A; Gine E; Chiappella A; Kluin-Nelemans HC; Jurczak W; Krawczyk K; Móciková, Heidi; Klener P; Šálek, David; Walewski J; Szymczyk M; et al. (Annals of oncology, 2013)
BACKGROUND: Central nervous system (CNS) involvement in mantle cell lymphoma (MCL) is uncommon, and the manifestations and natural history are not well described. PATIENTS AND METHODS: We present the data on 57 patients with MCL who developed CNS involvement, from a database of 1396 consecutively treated patients at 14 institutions. RESULTS: The crude incidence of CNS involvement was 4.1%, with 0.9% having CNS involvement at diagnosis. Blastoid histology, B-symptoms, elevated lactate dehydrogenase, Eastern Cooperative Group performance status >=2 and a high Mantle Cell Lymphoma International Prognostic Index score were enriched in the cohort with CNS involvement, and the presence of >=1 of these features defined a high-risk subset (an actuarial risk of CNS involvement 15% at 5 years) in a single-institution subset. The median time to CNS relapse was 15.2 months, and the median survival from time of CNS diagnosis was 3.7 months. The white blood cell count at diagnosis <10.9 x 109/l, treatment of CNS involvement with high-dose anti-metabolites, consolidation with stem cell transplant and achievement of complete response were all associated with improved survival. CONCLUSIONS: In MCL, CNS involvement is uncommon, although some features may predict risk. Once manifest outlook is poor; however, some patients who receive intensive therapy survive longer than 12 months.
Keywords: Central Nervous System; riziko; Aged; přežití; Survival; Treatment Outcome; Aged, 80 and over; Retrospective Studies; Risk; lidé středního věku; senioři; počet leukocytů; nádory centrálního nervového systému; lidé; Adult; Middle Aged; dospělí; Europe; Female; výsledek terapie; senioři nad 80 let; Leukocyte Count; Central Nervous System Neoplasms; ženské pohlaví; Lymphoma, Mantle-Cell; Male; protinádorové antimetabolity; Humans; mužské pohlaví; Antimetabolites, Antineoplastic; lymfom z plášťových buněk; Evropa; centrální nervový systém; retrospektivní studie